2021
DOI: 10.26444/aaem/122259
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and vascular disorders as para-occupational diseases – a Polish perspective

Abstract: Introduction. The study presents the difference between occupational and para-occupational diseases in terms of Polish law, and indicates the fact that cardiovascular diseases (CVDs) are considered to be work-related, and describes the latest reports on the prevalence of cardiovascular risk factors in workplaces. Objective. The aim of this study is to present the difference between occupational and para-occupational diseases in terms of Polish law. Also indicated is the fact that cardiovascular diseases (CVDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…There may be several explanations for this difference. Firstly, the HAB group had a higher mean age and the WOBASZ study demonstrated that SBP rises with age until about the age of 70 [10]. Secondly, achieving the degree of a postdoctoral fellow may be in itself stressful due to the highly competitive environment and challenging work.…”
Section: Discussionmentioning
confidence: 99%
“…There may be several explanations for this difference. Firstly, the HAB group had a higher mean age and the WOBASZ study demonstrated that SBP rises with age until about the age of 70 [10]. Secondly, achieving the degree of a postdoctoral fellow may be in itself stressful due to the highly competitive environment and challenging work.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there was a decrease in the number of disqualifications due to cardiovascular diseases, more noticeable compared to the main reasons for disqualification (Table 3, "A-E"), in the context of persistently high incidence and death rates due to these diseases. 31,32 It is possible that awareness of one's own cardiovascular health problems or treatment used 33 significantly influence these patients' decisions to donate blood, hence the decrease in such disqualifications (Table 3). What is equally positively surprising is the decrease in disqualifications of donors due to viral hepatitis (Table 3).…”
Section: Dovepressmentioning
confidence: 99%